Interlayer exchange coupling and interface magnetic anisotropy with crossed in-plane and perpendicular magnetic anisotropies - Hiroki Koizumi; Michio Hagihara; Soki Kobayashi; Hideto Yanagihara (AIP Advances, 2020)
We investigated interlayer exchange coupling (IEC) and interface magnetic anisotropy (Ki) between two ferromagnetic layers with crossed in-plane and perpendicular magnetic anisotropies separated by a non-magnetic spacer by using the anomalous Hall effect (AHE). The sample consisted of a Co0.75Fe2.25O4 layer with perpendicular magnetic anisotropy and a Fe layer with in-plane anisotropy, separated by a MgO layer with variable thickness. Since Co0.75Fe2.25O4 and MgO are insulators, the AHE signal only reflects the magnetization process of Fe. From this, we determined both IEC and Ki. A strong antiferromagnetic IEC was confirmed between Co0.75Fe2.25O4 and Fe. The strongest IEC of −1.1 mJ/m2 was observed for directly coupled Fe and Co0.75Fe2.25O4 for which Ki was −1.1 mJ/m2.